Effects of tai chi exercises - Zhang, Yuxi. (2012)
Tai Chi, or also called ‘Tai Chi Chuan’, originated in China about six hundreds years ago as a martial art, has slowly become a widely popular physical exercise due to known health benefits. Tai Chi practitioners believe that ‘Qi’ – the vital life energy, is generated by this body-mind exercise. However, due to lack of scientific definition for Qi, it remains more as an art than a science. In this paper, we investigate the scientific basis for Tai Chi to produce such interesting health benefits. Electrical